PROJECT-BASED LEARNING AS A METHOD OF TEACHING ENGLISH - Голуб, Татьяна (Modern engineering and innovative technologies, 2017)
The article is devoted to the study of project-based learning basics and its use in teaching English in university. The project method is a way to achieve a didactic goal through the detailed development of a problem, which should be completed with a very